1999
DOI: 10.1037/0021-843x.108.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathy across cultures: North America and Scotland compared.

Abstract: Differences in the prevalence and presentation of psychopathic personality disorder between North America and Scotland were evaluated. R. D. Hare's (1991) Psychopathy Checklist-Revised ratings obtained from a sample of 2,067 North American male prisoners and forensic patients were compared with ratings obtained from 246 Scottish male prisoners. Item response theory methods were used to examine differences in the performance of items and to equate the scale across settings. The items had equal relevance to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
191
2
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(200 citation statements)
references
References 23 publications
(57 reference statements)
6
191
2
1
Order By: Relevance
“…All participants completed diagnostic and PCL-R inter views and authorised access to their criminal records. A cross-cultural validation study 23 of the PCL-R demon strated that cutoff scores for psychopathy in men vary between North America (30 of a possible 40 points) and Europe (25 of a possible 40 points). We used a score of 25 as the threshold for psychopathy.…”
Section: Participants and Study Designmentioning
confidence: 99%
“…All participants completed diagnostic and PCL-R inter views and authorised access to their criminal records. A cross-cultural validation study 23 of the PCL-R demon strated that cutoff scores for psychopathy in men vary between North America (30 of a possible 40 points) and Europe (25 of a possible 40 points). We used a score of 25 as the threshold for psychopathy.…”
Section: Participants and Study Designmentioning
confidence: 99%
“…Nevertheless, only one of these UK pooled samples was representative of an entire correctional jurisdiction, and the North American samples were more likely to come from high and medium security institutions. Cooke and Michie (1999) argued that sample selection did not explain the lower prevalence of psychopathy among Scottish prisoners.…”
Section: Prevalence Of Psychopathy Among Prisonersmentioning
confidence: 99%
“…205-210;Hare, Clark, Grann & Thornton, 2000) demonstrated lower PCL-R scores than North American samples. Based on Item Response Theory analyses (IRT), it was subsequently argued that, when making the diagnosis, the standard PCL-R cut score for psychopathy should be lowered for UK populations (Cooke & Michie, 1999;Cooke, Michie, Hart & Clark, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Interpersonal and affective features were described as the core factors of the ''psychopathic personality'' [8,32] and research with adults suggested that these were the most distinctive and defining aspects of the disorder [13]. Studies with male offenders [5,13,14] examined the item response theory (IRT) to test item functioning and concluded that the interpersonal/affective dimension was generally more discriminating and provided more information about the construct than behavioral items. Vincent and Hart utilized the IRT with adolescent boys: Their findings indicated that psychopathy in adolescent boys was a coherent construct and that there were some similarities in item functioning between male adolescents and adults [76].…”
Section: J Psychopathy In Youthmentioning
confidence: 99%
“…Method We examined 91 male and 123 female adolescent detainees (aged [14][15][16][17][18][19] for psychopathology -using the Youth Self Report, the Overt Aggression Scale-Modified and a Conduct Disorder Self Report Scale-and for psychopathic dimensions using the psychopathy checklist youth version (PCL:YV). Based on a linear regression analysis we compared the specific associations between psychopathology and psychopathy in both male and female delinquent juveniles.…”
mentioning
confidence: 99%